MGFp: an Open Mascot Generic Format parser library implementation - Kirchner, Marc; Steen, Judith A. J.; Hamprecht, Fred; Steen, Hanno (Journal of proteome research, 2010)
Despite the efforts of the mass spectrometry (MS) community to migrate data representation toward modern file formats, legacy text formats still play an important role in MS data processing workflows. We provide a formal grammar and a portable, efficient C++ implementation for a Mascot Generic Format (MGF) parser.
Gesehen am 14.03.2023